2022
DOI: 10.1101/2022.10.01.510473
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Overexpression of AMPKγ2 increases AMPK signaling to augment human T cell metabolism and function

Abstract: T cell-based cellular therapies benefit from a product with reduced differentiation and enhanced oxidative metabolism. Methods to achieve this balance without negatively impacting T cell expansion or impairing T cell function have proven elusive. AMP-activated protein kinase (AMPK) is a cellular energy sensor which promotes mitochondrial health and improves oxidative metabolism. We hypothesized that increasing AMPK activity in human T cells would augment their oxidative capacity, creating an ideal product for … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
1
0
0
Order By: Relevance
“…We found that AMPK-deficient Treg cells were unable to augment their oxygen consumption under the stress of a mitochondrial uncoupling agent ex vivo, failed to upregulate genes supporting mitochondrial metabolism in the TME, and did not sustain proper mitochondrial mass/membrane potential or metabolic homeostasis during viral pneumonia. These results credential AMPK as a key mediator of Treg cell metabolic adaptation to settings of microenvironmental stress, likely through potentiation of mitochondrial metabolism, and are consistent with in vitro experiments suggesting AMPK potentiates Treg cell suppressive function (40).…”
Section: Discussionsupporting
confidence: 82%
“…We found that AMPK-deficient Treg cells were unable to augment their oxygen consumption under the stress of a mitochondrial uncoupling agent ex vivo, failed to upregulate genes supporting mitochondrial metabolism in the TME, and did not sustain proper mitochondrial mass/membrane potential or metabolic homeostasis during viral pneumonia. These results credential AMPK as a key mediator of Treg cell metabolic adaptation to settings of microenvironmental stress, likely through potentiation of mitochondrial metabolism, and are consistent with in vitro experiments suggesting AMPK potentiates Treg cell suppressive function (40).…”
Section: Discussionsupporting
confidence: 82%